A product Meta Data Model of assembly-related extreme data to enable hybrid decision support - Gräßler, Iris; Vollenkemper, Felix; Pottebaum, Jens (1st International Symposium: March 24 – 26, 2026, Heinz Nixdorf Institute, Paderborn University)
Models of Circular Economy introduce circularity strategies like reuse, repair or remanufacture. A significant level of complexity is added when these strategies are applied not only on integrated product level, but on lower levels of assemblies and parts. Therefore, approaches, like Design for Assembly, Disassembly and Reassembly (DfADR) become increasingly important including the consideration of ADR capabilities. To put DfADR into practice, it is necessary to structure ADR-related product data and make it usable for product engineers. For instance, assemblies resulting from disassembly might not be consistent with original assembly structures. Therefore, a Product Meta Data Model (MDM) is required to handle assembly-related data even when it has extreme characteristics. A literature review on related MDMs reveals a range of models for general product data and identifies a gap in consideration of assembly-related data. In an expert workshop, requirements are raised to evaluate existing models and develop ADR-related extensions. The MDM is conceptually modelled and validated by competence questions. The paper presents an approach that makes assembly-related data usable for hybrid decision support and enables engineers to think ahead of ADR processes.

Evolving Design for Assembly, Disassembly and Reassembly into a new paradigm: Design-for-Capabilities with Hybrid Decision Support as an enabler for circular products - Gräßler, Iris; Pottebaum, Jens; Nyhuis, Peter; Schmidt, Matthias; Grewe, Benedikt; Vollenkemper, Felix; Hesse, Thomas; Meinecke, Tim (Stuttgarter Symposium für Produktentwicklung (SSP) 2025)